2023
DOI: 10.1177/23779608231174866
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Associated Factors Among Adult Cancer Patients Undergoing Chemotherapy Treatment at Amhara National, Regional State, Ethiopia, 2021

Abstract: Background In cancer, quality of life (QoL) is an important patient-reported metric; evaluating how patients feel physically and emotionally while fighting the disease could lead to better treatment. Despite its therapeutic effects, chemotherapy treatment causes a plethora of side effects that can affect QoL. Factors affecting the QoL of cancer patients undergoing chemotherapy treatment in Ethiopia have not been thoroughly investigated. As a result, this study assesses QoL and associated characteristics among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 51 publications
1
17
1
Order By: Relevance
“…Most (60.7%) of the participants had been affected by cancer or its symptoms. The participants who had good functional QoL were 42.6%, which was slightly lower than a study conducted in Gondar, Ethiopia, which reported that 44.8% of the participants had a good functional QoL score ( 19 ). The participants who had good overall health status and overall QoL were 54.8% and 31.7%, respectively.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Most (60.7%) of the participants had been affected by cancer or its symptoms. The participants who had good functional QoL were 42.6%, which was slightly lower than a study conducted in Gondar, Ethiopia, which reported that 44.8% of the participants had a good functional QoL score ( 19 ). The participants who had good overall health status and overall QoL were 54.8% and 31.7%, respectively.…”
Section: Discussioncontrasting
confidence: 58%
“…This finding was much lower than a similar study conducted in Gondar, Ethiopia, which reported that the mean QoL of patients with cancer was 52.7 with a standard deviation of 20.1 ( 18 ). A similar recent study conducted in the cancer centers of Amhara Regional State also reported a higher average QoL score of 44.32 ( 19 ). The mean score of the QoL of patients with cancer in this study was also much lower than the national pooled result of various studies in Ethiopia, which was 57.91 ( 30 ).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Nowadays, measuring QoL is common among cancer patients. Most research in Ethiopia revealed that cancer patients had poor QoL ( Abegaz et al, 2018 ; Hassen et al, 2019 ; Muhamed et al, 2023 ). Previous research has shown that low QoL is associated with undesirable treatment outcomes, such as mental illness, that is, anxiety, depression, and hopelessness, which may gradually worsen the prognosis and increase mortality rates ( Tesemma et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%